2021
DOI: 10.3390/plants10112410
|View full text |Cite
|
Sign up to set email alerts
|

Root Trait Variation in Lentil (Lens culinaris Medikus) Germplasm under Drought Stress

Abstract: Drought is the most critical environmental factor across the continents affecting food security. Roots are the prime organs for water and nutrient uptake. Fine tuning between water uptake, efficient use and loss determines the genotypic response to water limitations. Targeted breeding for root system architecture needs to be explored to improve water use efficiency in legumes. Hence, the present study was designed to explore root system architecture in lentil germplasm in response to drought. A set of 119 lent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Earlier several studies also demonstrated that root traits are complex in genetic architecture and many genes/QTLs along with high genotype x environment interactions are involved to control the root traits inheritance (Kumar et al, 2012;Priya et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier several studies also demonstrated that root traits are complex in genetic architecture and many genes/QTLs along with high genotype x environment interactions are involved to control the root traits inheritance (Kumar et al, 2012;Priya et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore knowledge of genetic variability for root traits can help to breed improved droughttolerant cultivars in lentil. Earlier significant variation for different root traits was observed among several lentil germplasm (Kumar et al, 2012;Priya et al, 2021). However, root traits are complex in genetic architecture, and many genes/ QTLs along with high genotype x environment interactions are involved to control the root trait inheritance.…”
Section: Introductionmentioning
confidence: 99%
“…When facing drought and salt stress, the organic carbon content of plant leaves and roots is affected to adapt to the impact of environmental water potential changes on plant growth ( Ulrich et al, 2022 ; Dell’Aversana et al, 2021 ; Priya et al, 2021 ). This study indicated that the organic carbon, total nitrogen, and total phosphorus contents of E. nutans leaves were all affected by the decrease in environmental water potential.…”
Section: Discussionmentioning
confidence: 99%
“…Root morphology could be regulated by environmental conditions, i.e., climate and soil fertility [31][32][33]. Under drought or nutrient-limiting, conditions lentils may develop longer root systems to scavenge available soil moisture or nutrients [34,35]. Considering that all lentil genotypes were cultivated under the same conditions in proximity, the landrace Eglouvis samples, which exhibited a longer root system, could withstand longer drought conditions and tolerate nutrient-poor soils.…”
Section: Plant Traits Impact Microbial Diversitymentioning
confidence: 99%